A theoretical study of the optical properties of nanostructured TiO2 - Fuertes, Valeria Cintia (2013)
Optical properties of TiO2 nanoclusters (with more than 30 TiO2 units) were calculated within a fully atomistic quantum dynamic framework. We use a time dependent tight-binding model to describe the electronic structure of TiO2 nanoclusters in order to compute their optical properties. We present calculated absorption spectra for a series of nanospheres of different radii and crystal structures. Our results show that bare TiO2 nanoclusters have the same adsorption edge for direct electronic transition independently of the crystal structure and the nanocluster size. We report values of the adsorption edge of around 3.0 eV for all structures analyzed. In the present work we demonstrate that, for small clusters, both the direct transition absorption edge and the blue shifting phenomena are masked by thermal disorder.